Perceptions of aging across 26 cultures and their culture-level associates - Löckenhoff, Corinna E. (Array, 2009)
Perceptions of aging were examined in 26 cultures. Samples within each culture filled in peer report version of NEO-PI-R specially designed for assessment of adolescent personality. Results are analyzed in order to estimate perceived age differences in personality.